Preparation, characterization, and optimization of primaquine-loaded solid lipid nanoparticles - Omwoyo, Wesley Nyaigoti; Ogutu, Bernhards; Oloo, Florence; Swai, Hulda; Kalombo, Lonji; Melariri, Paula; Mahanga, Geoffrey M.; Gathirwa, Jeremiah Waweru (PMC, 2014)
Primaquine (PQ) is one of the most widely used antimalarial drugs and is the only available drug that combats the relapsing form of malaria. PQ use in higher doses is limited by severe tissue toxicity including hematological- and gastrointestinal-related side effects. Nanoformulation of drugs in an appropriate drug carrier system has been extensively studied and shown to have the potential to improve bioavailability, thereby enhancing activity, reducing dose frequency, and subsequently reducing toxicity. The aim of this work was to design, synthesize, and characterize PQ-loaded solid lipid nanoparticles (SLNs) (PQ-SLNs) as a potential drug-delivery system. SLNs were prepared by a modified solvent emulsification evaporation method based on a water-in-oil-in-water (w/o/w) double emulsion. The mean particle size, zeta potential, drug loading, and encapsulation efficiency of the PQ-SLNs were 236 nm, +23 mV, 14%, and 75%, respectively. The zeta potential of the SLNs changed dramatically, from −6.54 mV to +23.0 mV, by binding positively charged chitosan as surface modifier. A spherical morphology of PQ-SLNs was seen by scanning electron microscope. In vitro, release profile depicted a steady drug release over 72 hours. Differential scanning calorimeter thermograms demonstrated presence of drug in drug-loaded nanoparticles along with disappearance of decomposition exotherms, suggesting increased physical stability of drug in prepared formulations. Negligible changes in characteristic peaks of drug in Fourier transform infrared spectra indicated absence of any interaction among the various components entrapped in the nanoparticle formulation. The nanoformulated PQ was 20% more effective as compared with conventional oral dose when tested in Plasmodium berghei-infected Swiss albino mice. This study demonstrated an efficient method of forming a nanomedicine delivery system for antimalarial drugs.
Keywords: double emulsion; nanomedicine drug-delivery system; antimalarial; nanotechnology